Dealing with disasters: Flood, famine and mobile phones. (Economist, 2007)
Humanitarian relief is being transformed by technology. Once, when a disaster struck, big aid agencies would arrive and hand out grain, blankets, and medicine to victims who struggled to relief camps. Now, computer technicians are often the first people on the scene, setting up telephone networks so that aid agencies can do their jobs. Disaster relief is basically an enormous logistics operation, and today's emergency responders use technology in much the same way as other delivery providers. Donors use spreadsheets to track supplies and communicate with each other using text messages; aid suppliers can find out exactly where on an inbound ship their supplies are stored, saving hours of waiting at the docks. However, although the benefits of technology to the aid workers may appear obvious, its effect on recipients is yet to be determined.